Retrospective Analysis for Taste, Tolerability and Efficacy Within a Low Calorie Diet with Spaghetti for Special Medical Purposes (Afms) - Tarro, Giulio; Tuoro, Francesco di; Folco, Anna; Caprio, Veronica Di; Corato, Valentina; Felice, Bruna De; Montanino, Concetta (British Journal of Healthcare and Medical Research, 2022)
The maintenance and control of body weight loss are finely regulated by the interaction of a series of biochemical processes, which include homeostatic, environmental and behavioral factors. To maintain weight loss during over time, subjects must become aware of the physiological adaptations, which would favor their recovery, and then apply dietary strategies capable of modulating insulin, tryptophan, ghrelin and leptin, hormones that intervene to reduce the dreaded 'yo -yo effect'. Spaghetti plays an important role in human nutrition, also in nutritional programs for weight loss or maintenance because it is considered a balanced food in diets for calorie content, about 360 Kcal / 100gr, for low-medium glycemic index and for frequent use in Italian cuisine. The nutritional properties of spaghetti can improve and vary considerably in relation to the ingredients, drawing, rolling and drying. There are many works concerning the integration of pasta products obtained from wheat with unconventional raw materials with a high content of micronutrients and for this reason we realize how pasta, given its widespread use, ease of use, its shelf life and its intrinsic food value (Antognelli, 1980) can be improved with nutritional principles to be considered as a functional food.